Aflasafe product ZM01 and ZM02 for Zambia - CGIAR Research Program on Agriculture for Nutrition and Health (2017)
Aflasafe ZM01 and Aflasafe ZM02, two biocontrol products developed for use in maize and groundnut in Zambia, were approved by the regulatory authority Zambia Environmental Management Agency (ZEMA) in 2018. Both products are ready for uptake by a private sector company.